Atraumatic perspectives of ART: psychological and physiological aspects of treatment with and without rotary instruments - Schriks MCM, van Amerongen WE. (Blackwell Synergy, 2003)
Atraumatic Restorative Treatment, ART, is a method of minimal caries intervention that uses only hand instruments. The aim of the present study was to explore a possible difference between the extent of discomfort experienced during dental treatment according to the ART approach and a method using rotary instruments.